1-A-D-24. Source-level analysis of brain oscillatory activity using hilbert transformation. Issue 6 (June 2015) - Matsubayashi, Jun; Tominaga, Wataru; Matsuhashi, Masao; Mima, Tatsuya; Fukuyama, Hidenao; Mitani, Akira
Abstract : We have developed a tool for source-level analysis of brain oscillatory activity using hilbert transformation. The objective of this study was to test the availability of this tool with a real data set. Magnetoencephalographic signals were recorded from ten healthy volunteers. Median nerve was electrically stimulated at the right wrist 100–150 times. Raw signals were high-pass (8 Hz cutoff) and low-pass (13 Hz cutoff) filtered, and each single-trial signal consisting of 8–13 Hz oscillation was extracted. Source estimation of each signal was performed with SPM8. The envelope and instantaneous phase were calculated using hilbert transformation, on the basis of each single-trial source waveform. Averaging these envelopes, we obtained the amplitude modulation of alpha oscillation from each dipole. We also calculated time course of phase difference between the seed dipole at the left postcentral gyrus and each dipole in the cortex. The amplitude of alpha oscillation at the left postcentral gyrus began to decrease at around 200 ms; this finding was consistent with previous literature. Trial-to-trial variation of phase difference was small in the dipoles near the seed dipole, and in the dipoles on the right precentral gyrus. Therefore, this tool allows us to perform frequency analysis on the source level, skipping sensor-level analysis.